Digital-based Career Specialization Service is an Innovative Counseling Service for Counseling Teachers of Junior High Schools - Ririanti Rachmayanie Jamain; Rizka Amalia; Isma Isma (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Choosing the right career specialization significantly affects students' future life prospects. However, the career specialization service provided by the Guidance and Counselling (GC) teachers remains suboptimal due to the continued reliance on manual instruments, which results in protracted analysis periods. One challenge GC teachers face is their limited proficiency in utilizing technology to digitize instruments. The objective of providing training on digital-based career guidance services is to assist counseling teachers in analyzing career guidance instruments. Digital-based career guidance service training was provided to 26 counselling teachers who are MGBK SMP Barito Kuala Regency members with brain storming and hands-on practice methods guided by the Mandatory Research Lecturer Program team. The training yielded a 75% improvement in technology-related proficiencies, meaning counseling teachers are capable of implementing this digital career specialization service within their respective academic institutions.